Creating Partnerships with Parents: An Educator's Guide - Lueder, Donald (Rowman & Littlefield Publishers, 2000)
Are you wondering how to nurture a better relationship with the parents of your students? This book provides teachers with comprehensive methods to bridge the gap between school and home in order to enhance the development of their students.